2015
DOI: 10.1111/een.12258
|View full text |Cite
|
Sign up to set email alerts
|

Does the host plant affect the benefits from mutualisms?The invasive mealybug and ghost ant association

Abstract: 1. The benefits to trophobionte hemipterans are affected by the ant tending level, which is a widely accepted statement. The ant tending level is closely related to multiple factors. It is clear that the ant tending level can be affected by the temporal factor, age-specific, the density of the hemipterans, and quantity and quality of honeydew produced by hemipterans.2. Few studies of ant-hemipteran mutualisms have reported the patterns of host plants-dependent effects, and whether host plants influence the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Herbivore‐induced plant volatiles proved very attractive to several larval parasitoids and arthropod predators (McCormick et al ., ; Cusumano et al ., ; Xu et al ., ). Our previous study also revealed that in comparison with healthy cotton plants, A. bambawalei had an obvious preference for plants infested by mealybugs (Zhou et al ., ). Some research has suggested that chemical cues play an important role in host location by natural enemies and these reported chemicals are mainly derived from host plants (Arimura et al ., ; Dicke & Baldwin, ; Ponzio et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Herbivore‐induced plant volatiles proved very attractive to several larval parasitoids and arthropod predators (McCormick et al ., ; Cusumano et al ., ; Xu et al ., ). Our previous study also revealed that in comparison with healthy cotton plants, A. bambawalei had an obvious preference for plants infested by mealybugs (Zhou et al ., ). Some research has suggested that chemical cues play an important role in host location by natural enemies and these reported chemicals are mainly derived from host plants (Arimura et al ., ; Dicke & Baldwin, ; Ponzio et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…() and Zhou et al . (). Each treatment had 60 replications each with different group of parasitoids.…”
Section: Experimental Designmentioning
confidence: 97%
See 3 more Smart Citations